The challenge of ethical leadership university courses: preparing leaders for an uncertain, turbulent and divert future (Revista Lusófona de Educação, 2015)
This paper discusses the necessity of introducing Ethical Leadership in university leadership preparation courses and provides an example of designing and implementing such a course. Emphasis is given on the teaching methodology of the course which is based on experiential learning, a combination of action and case study research approaches and an intermingling of open and traditional teaching practices. The structure of the proposed course draws upon extensive relevant literature review and attempts to incorporate the main strands of adult education. A students’ self-evaluating tool is also included as a means to evidence the course participants’ satisfaction as well as to help feedback and further enquiry. The rationale behind this course proposal is that, instead of trying to change or eradicate misappropriate leadership concepts and values at a later age, it is much better to care for their good formation and foundation as earlier as possible, during [head]teacher initial formation [at university level]. Keywords: ethical Leadership; university course; experiential learning; school leaders.